Redesain Identitas Visual Pantai Panjang sebagai Media Penjenamaan Pariwisata Pesisir di Kota Bengkulu - Martadireja, Sonde (Prahasta Publisher (manage by: DRPM Institut Bisnis dan Teknologi Indonesia), 2024)
Branding is defined as the process of strengthening a product through a brand. Although initialy closely related to economics, branding now extends to various fields and has become one of the key elements in modern communication. This research focuses on redesigning the visual identity of Pantai Panjang in the city of Bengkulu. The goal is unlock more coastal tourism potential of Pantai Panjang through well-planned graphic design, thereby facilitating visual communication to support branding. This research uses a qualitative method with a creative production approach. Data is obtained through observation, interviews, and documentation. The fishbone method is used to analyze the main issues, which is then followed by the SMART method to determine the appropriate redesign decisions. The redesign is based on visual elements and principles. The use of cultural narratives (surat ulu) in typography, natural icons of Bengkulu (rafflesia arnoldi flower), and coastal nature in illustrations are strengthened by the principles of balance, emphasis, and unity. The redesign result include a logo that can be implemented across various communication media. Consistent broadcasting, being up-to-date, and active participation of all related elements will be an effective communication strategy in this branding effort.